Making Singapore a regional centre for philanthropy - OW, Kim Kit (Institutional Knowledge at Singapore Management University, 2022)
The article highlights the strong ecosystem in Singapore where charitable initiatives are supported and encouraged, and builds on DPM Lawrence Wong's recent comments that the Government is reviewing its tax incentive schemes to encourage increased philanthropic giving.As a starting point, we suggest three simple ways in which tax incentives could be enhanced:1) increasing the enhanced tax deduction for donations from the current 2.5 times the amount of qualifying donations to 3 times for certain causes where there is a significant amount of public spending;2) extending the period for which tax deductions for donations can be carried forward for from the current 5 years, perhaps indefinitely; and3) consider allowing some tax deductions for donations for selected overseas charitable causes.These suggestions would build on the existing generous tax incentive schemes for philanthropy, such as the exemption on the income of the foreign account of a philanthropic purpose trust (administered by a trustee company in Singapore) and the not-for-profit organisation tax incentive administered by the Economic Development Board.No doubt, more sophisticated initiatives are currently in the pipeline and we look forward to them being announced soon.Finally, the article notes that donors are more likely to be driven by a desire to make a difference in the world rather than to maximise tax savings. As such creating a strong framework for reporting and monitoring the real-world impact of donations is likely to further encourage philanthropy.